Bentuk Penyajian Tari Dampeng Pada Upacara Adat Pernikahan Di Kecamatan Longkib Kota Subulussalam Aceh Singkil - Murniati Murnianti; Zora Iriani; Desfiarni Desfiarni (SENDRATASIK UNP, 2019)
This article aimed to describe the form of Dampeng Dance Presentation at a Traditional Wedding Ceremony in the Sub-District of Subulussalam Longkib, Aceh Singkil, by revealing the form and sequence of Dampeng dance at the Traditional Wedding Ceremony. The type of this research was qualitative using descriptive methods. The object of this research was the Form of Dampeng Dance Persentation at a Marriage Ceremony in the Sub-District of Longkit, Aceh Singkil. The types of data in this study were primary data and secondary data, with research instruments namely the researcher herself. Since the research was a library research, the techniques of data collection were observation, interviews and documentation. After collecting the data, the data was analyzed accurately and selected according to the needs and its relation to the issues discussed. The results showed that Dampeng dance was a traditional dance that grew and developed in the Longkib Subdistrict, Subulussalam. The form of Dampeng dance was a combination of the imitation of an eagle that is spinning overhead. The form of presentation of the Dampeng dance at this ceremony was a symbolic form, because it was a part of the conclusions in enlivening the wedding ceremony. Dampeng dance is a symbol of wedding ceremony and describes cooperation in social community. Besides a movement, Dampeng dance also conveys messages to the listener about the meaning of life, kindness, politeness, advice and caring for each other.